Capturing tacit knowledge for assessing employees' competency and productivity - A. Jabar, Marzanah; Sidi, Fatimah; Selamat, Mohd Hasan; Abd Ghani, Abdul Azim; Ibrahim, Hamidah; Baharom, Salmi (Science Publications, 2011)
Problem statement: Organization has to evaluate the competencies of their workers to improve organizational productivity. However, this is difficult because organizations have difficulties to capture and retain knowledge especially tacit knowledge of their employees. Approach: The study reviewed selected literature on management knowledge and employers competencies. It also reviewed existing frameworks in knowledge management focusing on the capturing and storing tacit knowledge. Results: Results of this study will include theoretical concept for capturing tacit knowledge and storing them besides developing a model for measuring employee’s competencies in the organization. Conclusion/Recommendation: This study contributes in assessing knowledge workers performance to improve their productivity in an organization.